Contribution to the study of available boron soils of the state of S. Paulo, Brazil: I . Growth and mineral composition of sunflower (Helianthus annus Mill.) - Ruy, V. De Moraes; Brasil Sobrinho, M.O.C.; Malavolta, E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
Sunflower plants were grown in the greenhpuse in five soil series of the Piracicaba Country, S. Paulo, Brazil (Terra Roxa Estruturada, TRE; Roxo Latosol, LR; Red Latosol, LV; Red Yellow Podzolic: PVA- Quartz sand, AQ), under seven rates of B (from 0 to 1 ppm). A visual assessment, based on the age of the plants when first symptoms of B deficiency showed up, disclosed that the PVA had the lowest available B concentration being followed by LV, AQ, TRE and LR. Insolar as growth data are concerned it has been found that plant heightt was the characteristic showing higher correlation with available B in the soil. The tissue concentration of P, Mg, and B consistently increased at low levels of boron in the soil. The leaf concentration of Cu, Fe, Mn, and Zn was unaffected by the B supply, the reverse being true, however, in the case of boron. The concentration of B in young leaves (upper third of the plant), among all organs (roots, stems, older leaves) analysed provided the best correlations with the availability of the micronutrient under study.